MENGUNGKAP PENERAPAN AKUNTANSI LINGKUNGAN PADA RUMAH SAKIT UMUM DAERAH KOTA AMBON - Gasperz, Jefry; Kriswantini, Dwi (Jurnal Akuntansi, 2021)
This research aims to illustrate the phenomenon and facts about the application of environmental accounting conducted by the management of the District General Hospital (RSUD) of Dr M Haulussy Ambon in an effort to reduce the environmental impact caused by activities of hospital operations, as well as evaluating the suitability of environmental accounting reporting conducted by hospital management.This research is a type of qualitative study with interpretative approach. The Data obtained in this study use interviews methods, observation, and archival sources. Data analysis uses a descriptive interpretive approach with analysis strategies and stages developed by 2003) which include data reduction, understanding and testing, and interpretation.The results showed that the management of the hospital Dr M Haulussy Ambon has been carrying out environmental management activities especially the waste treatment of hospitals has done well. In connection with the evaluation of Conformity reporting environmental accounting management RSUD has not done the environmental cost classification specifically in financial reports, environmental costs (such as waste processing costs) arising in the transactions Conducted by hospital management is still recognized at the time of transaction or during cash withdrawal. The environmental cost measurement in the hospital refers to the realization of the previous year's budget and is assessed for the cost incurred. Environmental costs presented with other similar accounts as the burden of goods and services, fixed assets, expenditure on operations and capital expenditure in financial statements are the realization reports of regional budget and expenditure budgets, operational reports, and balance sheets. The hospital has not disclosed a policy specifically regarding environmental costs in the records of the financial statements and is still grouped with other operational costs.